School Management Transformation Toward Digital Learning in Basic Education - Athiyyah Muanifah; Mohammad Syahidul Haq (Journal of Innovation and Research in Primary Education, 2026)
The ever-changing digital world impacts processes of learning. This study explores the possible school administration roles in digital technologies integration while maintaining values in the 5.0 Industrial Revolution period. Using a qualitative approach, the author employs a literature review and interviews a few school administrators to collect and analyze the data and information pertaining to the acquisition of technology, the training and education of teachers, and the resolution of problems relating to the technology, the equipment, the teaching resources, and the technological infrastructure. The data reveals that school administrators should be proactive in the areas of technology management, the systematization of structures and processes, the organization of administrative training and educational activities, and the creation of a school environment that emphasizes innovative technology. To be effective, educational systems, and the values that guide them, must evolve. The author asserts that in order to digital transformation in education sustain, cross-sector partnerships must be made to elaborate imbalanced access to technology and systems of data-drive evaluation to all stakeholders.